Book inventory system using RFID - Nurul Nadia, Mat Jalaluddin (2011)
Radio-frequency identification (RFID) is a technology uses communication via electromagnetic waves to exchange data between a terminal and an object such as a product, animal, or person for the purpose of identification and tracking. Among the many uses of RFID technology is its deployment in libraries.This technology has slowly begun to replace the traditional barcodes on library items (books, CDs, DVDs, etc.).The RFID tag can contain identifying information,such as a book's title or material type, without having to be pointed to a separate database.The information is read by an RFID reader, which replaces the standard barcode reader commonly found at a library's circulation desk. In this project, RFID technology will help the management of the library and also the customer for library in order to manage the inventory and all the transaction process happen eiery day. This technology also reduces time and increase the efficiency.Therefore, it will make the data of the library can be view and manage more systematically by the administrator or staff.